Co-mutations of TP53 and KRAS serve as potential biomarkers for immune checkpoint blockade in squamous-cell non-small cell lung cancer: a case report - Cheng Fang; Chu Zhang; Wei-Qing Zhao; Wen-Wei Hu; Jun Wu; Mei Ji (BMC, 2019)
Abstract Background Unprecedented durable responses are identified in clinical studies to target the signaling of programmed cell death protein-1 (PD-1) as well as its ligand (PD-L1) in patients with squamous-cell non-small cell lung cancer (NSCLC). However, factors predicting the patient subtypes that are responsive to PD-1/PD-L1inhibitors have not been fully understood yet. Biomarkers, like PD-L1 expression, tumor mutational burden(TMB), DNA mismatch repair deficiency (dMMR), and tumor-infiltrating lymphocytes (TILs), have been utilized to select patients responsive to PD-1/PD-L1inhibitors in the clinic, but each of them has limited use. Lung adenocarcinoma patients with a mutation of TP53 or KRAS, particularly those with co-mutations of TP53 and KRAS, can benefit from anti-PD-1 treatment. Case presentation In this study, the co-mutations of TP53 and KRAS in a 64-year-old non-smoking man with squamous-cell NSCLC patient was described using the next-generation sequencing (NGS) technology. The patient was treated with the pembrolizumab combined with gemcitabine as the salvage therapy, and a marked partial response could be attained, which had persisted for over 7 months. Conclusion In addition to testing common driving genes, like EGFR, ALK, ROS1 and BRAF, both TP53, and KRAS should also be considered in advanced or metastatic squamous-cell NSCLC.TP53 and KRAS co-mutations in squamous-cell NSCLC can be a potential factor to assess possible response to PD-1 blockade immunotherapy, but further studies with more cases are needed to confirm the prediction power.